THE STUDY OF STUDENTS’ PERCEPTION TOWARDS PRINCIPLE OF ACCOUNTING (PA): A SURVEY AMONG BUSINESS STUDENTS - Illias, Azleen; Yasoa, Mohd Rushdan; Abd Rahman, Rahida; Abd Razak, Mohd Zulkeflee (International Business Education Journal, 2009)
The Principle of Accounting (PA) subject is a core course in most business faculty or department. However, only limited research has examined the perceptions of business students about the accounting course relative to their respective majors. This study examines the differences perception of interest and important and also difficulty and confidence level of the students according to major programmes, accounting experience and non-accounting experience as well as gender. A short questionnaire was distributed to 306 business students in Universiti Malaysia, Sabah, Labuan International Campus. By employing an ANOVA, the result shows significant differences among gender and accounting experience relating to level of important and interest. Significant differences were also found in the level of difficulty and confidence relating to the courses registered among five major programmes. Besides, accounting experiences students perceived more confident in taking the course compared to non-experience student. The implication of this study suggest that non-experience students must be provided with clear explanation and encouragement to increase their perceived level of important, interest and confidence in taking this course.